MILITARY PATRIOTISM AS A SOCIO-PHILOSOPHICAL PHENOMENON IN THE CONTEXT OF GLOBAL SECURITY TRANSFORMATION (2015–2025) - К.Аминжонов (Modern American Journals, 2025)
The article is devoted to the philosophical analysis of military patriotism as a complex socio-cultural and axiological phenomenon formed in the context of the transformation of global threats and changes in the structure of international security in 2015–2025. The need to revise the traditional models of patriotic education and the formation of a new paradigm of "responsible patriotism" focused on humanistic values and civic maturity is substantiated.
Keywords: Military patriotism; national identity; civic responsibility; hybrid conflicts; digital security; patriotic education; civil society; information security; humanistic values; global security; political culture; social sustainability; collective identity.